Association of neonatal red blood cell transfusion with increase in serum bilirubin. Issue 12 (4th June 2014) - Christensen, Robert D.; Baer, Vickie L.; Snow, Gregory L.; Butler, Allison; Ilstrup, Sarah J.
<x xml:space="preserve">Abstract</x> Background It is not clear whether red blood cell (RBC) transfusions typically increase a neonate's total serum bilirubin (TSB) level or if so by how much. Study Design and Methods In this retrospective analysis, from 2009 through 2012, we collected TSB measurements before and after transfusions, recording blood types of mothers, neonates, and blood donors and whether phototherapy was used before, during, or after transfusion. Results Of 7272 neonates admitted during this period, 658 (9%) received 2597 RBC transfusions. TSB levels were drawn before and after 431 transfusions, 255 of which did not have phototherapy at the time the transfusion was administered. The mean increase in TSB was 2.2 mg/dL (95% confidence interval, 1.9‐2.5 mg/dL). Seven percent of all transfusions and 12% of transfusions to very‐low‐birthweight (VLBW) infants (<1500 g) were followed by a TSB increase of at least 5 mg/dL. Transfusions with "universal donor" blood (O–) resulted in a higher TSB increase (p < 0.0001), but the magnitude was clinically insignificant (0.3 mg/dL). Older blood (days since donor draw) did not generate significantly higher posttransfusion TSB levels (p = 0.092). A focused study of the 10 neonates with the highest TSB increases revealed that six were unexplained other than transfusion related. Conclusions We describe an association between RBC transfusion and TSB elevation, but we recognize that this does not establish a cause‐and‐effect relationship. However, the observation that an increase of at least 5 mg/dL occurs after 12% of transfusions to VLBW neonates suggests to us that clinicians will want to evaluate jaundice, or measure bilirubin, on VLBW neonates after transfusion.